Stackelberg competition between merchant and regulated storage investment in wholesale electricity markets - Huang, Qisheng; Xu, Yunjian; Courcoubetis, Costas (Applied energy, 2020)
•Construct a Stackelberg model to explore the competition in energy storage investment.•Social planner always obtains zero storage profit under linear storage investment cost.•Numerical experiments comparing different market settings with real-world data.•Insights provided for wholesale electricity market operation and design. We investigate the interaction between the regulated and merchant storage investment made by the social planner and a merchant, through a Stackelberg competition model. In the upper level, the merchant storage owner maximizes its profit through storage investment decisions. Given the merchant storage investment, the social planner makes its own regulated storage investment, overall storage operation, and economic dispatch decisions to minimize the overall system cost in the lower level problem. Both the merchant and regulated energy storage is remunerated based on the inter-temporal difference in locational marginal prices (solved by the lower level problem). We show that the regulated storage profit (of the social planner) is always nonnegative if the storage investment cost is convex in the installed storage capacity with no fixed cost. In particular, the regulated storage profit must be zero (non-positive) if the storage investment cost is linear (affine, respectively) in the installed storage capacity. Numerical results (on the IEEE 57-bus test system) with real-world load data from the California Independent System Operator (CAISO) show that Stackelberg competition between merchant and regulated storage investment can reduce 2–3% of social cost compared to a market without storage. We also show that the merchant (profit-maximizing) investment can significantly reduce the social planner’s expense in storage investment, at the cost of only 0.5% increase in social cost (compared to the socially optimal investment). These results suggest that the government shall encourage merchant companies to invest on energy storage and to participate in wholesale electricity markets.